Disability hate crime: persecuted for difference. (31st August 2016) - Ralph, Sue; Capewell, Carmel; Bonnett, Elizabeth
Abstract : This article briefly discusses the long history of violence towards disabled people which sets the context for an analysis of the modern‐day form of violence known as disability hate crime (DHC). People who look or behave differently to others often find themselves victims of violent crimes. The language used to describe disabled people contributes to their diminished position in society. A brief review of definitions of DHC and exploration of news media coverage of the Pilkington and Askew DHC cases are undertaken. Cultural scapegoating of disabled people is discussed. Disabled people are perceived as contributing to their own victimisation, the lack of support afforded to them by society and the failure of systems meant to protect them. As long as disabled people remain outside mainstream society, they are unlikely to achieve the same levels of respect and protection from crime that other groups in society are afforded.